STUDY OF FOOD WASTE AND PATIENTS LEVEL OF SATISFACTION TOWARD FOOD SERVICE IN THE CLASS III IN PATIENTS ROOM GAMBIRAN HOSPITAL KEDIRI CITY - Dewi, Nirwana Rose Mala (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The hospital nutrition service aims to improve the quality of hospital services to provide nutrition services that are efficient and integrated with other health services. The purpose of this study was to determine food waste and the level of patient satisfaction in the class III in patient room of Gambiran Hospital, Kediri City. The research method used was descriptive quantitative. With a total of 327 food waste respondents in this study patients with regular food and TKTP diet with age category 18-25 years. Characteristics of patients based on gender most of them are male, in total 176 people (54%) and female as many as 151 people (46%).The average total score of patient food waste in 1 cycle are 10 days, total average of patient food waste is 23%. the score has not met the minimum standard of patient food waste based on the Ministry of Health which is ? 20%. The results of patient satisfaction were 79.70% of patients expressed satisfaction with hospital food services.